Peran Pembelajaran Berbasis Masalah terhadap Penguasaan Konsep dan Tanggung Jawab Siswa Kelas IV pada Materi Daerahku dan Kekayaan Alamnya - Arum, Erin Giri; Sujana, Atep; Isrokatun, I. (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2024)
The low understanding ability of students in learning science and science is the main factor in conducting this research. This is due to the lack of meaningfulness in science learning. This research aims to determine the increase in students' mastery of concepts and responsibilities after implementing problem-based learning. The method used in this research is a quasi-experimental design with a Non-Equivalent Control Group design. In this study, the population in Cimahi City was taken and the sample used in this study was grade IV elementary school students in one of the schools in Cimahi Tengah District. Learning outcome tests, questionnaires and documentation are some of the data collection techniques used. Data were processed using the SPSS 23 application with normality test, homogeneity test, paired sample T test, independent sample T test and n-gain test. The results of this research show that class IV students' mastery of concepts has improved results between the experimental class that received treatment and the control class that did not receive treatment. Likewise, the responsibilities of class IV students have increased before implementing problem-based learning and after implementing this learning model.